Estimation of disease activity in patients with ankylosing spondylitis in the real practice of a rheumatologist in Russia (Part 2) - Evgeny Vladimirovich Volnukhin; E A Galushko; A G Bochkova; A V Smirnov; Sh F Erdes (Научно-практическая ревматология, 2012)
Objective: to compare different methods for estimating ankylosing spondylitis (AS) activity in the real practice of a rheumatologist in the Russian Federation. Subjects and methods. The investigation enrolled 464 patients with AS, who had consecutively visited rheumatologists for 4 months in 24 cities and towns of Russia. A specially designed clinical card was filled out for all patients. BASDAI and ASDAS scores were estimated by a physician and erythrocyte sedimentation rate (ESD) and C-reactive protein (CRP) were measured in all the patients. Mini-BASDAI scores were determined in patients with axial AS. The diagnosis of the disease was verified at the Research Institute of Rheumatology, Russian Academy of Medical Sciences, according to the 1984 modified New York criteria, by including X-ray film estimation. All activity assessment methods were compared. Results. The valid diagnosis of AS was confirmed in 330 (71.1%) out of all 464 patients included into the study; axial AS was present in 178 of them; their mean age was 39.7+10.2 years; the mean duration of disease was 14.6+2.6 years; 86% were men and 14% were women. About 61 and 74% of the patients (n = 178) had high BASDAI and mini-BASDAI scores, respectively; 88% had high and very high ASDAI (ESR) scores; the mean ESR (Westergren method) was 33.8+29 mm/h and CRP (n = 249) was 30 mg/l. Conclusion. On assessing the activity of disease, rheumatologists are primarily oriented to total activity scores and blood acutephase indicators (ESR and CRP) in real clinical practice. Patients with high disease activity calculated from BASDAI and ASDAS scores proved to be more. In its turn, ASDAS more frequently reveals high AS activity than BASDAI.